2011
DOI: 10.1152/physrev.00060.2009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Blood Pressure and Salt Homeostasis by Endothelin

Abstract: Endothelin (ET) peptides and their receptors are intimately involved in the physiological control of systemic blood pressure and body Na homeostasis, exerting these effects through alterations in a host of circulating and local factors. Hormonal systems affected by ET include natriuretic peptides, aldosterone, catecholamines, and angiotensin. ET also directly regulates cardiac output, central and peripheral nervous system activity, renal Na and water excretion, systemic vascular resistance, and venous capacita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
461
1
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 373 publications
(483 citation statements)
references
References 839 publications
(1,320 reference statements)
9
461
1
12
Order By: Relevance
“…A recent study suggests that bilateral adrenocortical hyperplasia is an almost ubiquitous finding in cats >9 years (97%), but there was no significant difference in histopathologic grading between hypertensive (n = 37) and normotensive cats (n = 30), supporting that adrenocortical hyperplasia is unlikely to be a primary factor in feline hypertension 13. A number of other factors have been demonstrated to modulate aldosterone production apart from angiotensin II including extracellular potassium concentration, adrenocorticotropic hormone, adrenomedullin, atrial natriuretic peptide, dopamine, endogenous digitalis‐like factors (eg, ouabain) and endothelin‐1, but the effect these play in regulating aldosterone production in the cat has not been investigated 24, 25, 26, 27, 28, 29…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggests that bilateral adrenocortical hyperplasia is an almost ubiquitous finding in cats >9 years (97%), but there was no significant difference in histopathologic grading between hypertensive (n = 37) and normotensive cats (n = 30), supporting that adrenocortical hyperplasia is unlikely to be a primary factor in feline hypertension 13. A number of other factors have been demonstrated to modulate aldosterone production apart from angiotensin II including extracellular potassium concentration, adrenocorticotropic hormone, adrenomedullin, atrial natriuretic peptide, dopamine, endogenous digitalis‐like factors (eg, ouabain) and endothelin‐1, but the effect these play in regulating aldosterone production in the cat has not been investigated 24, 25, 26, 27, 28, 29…”
Section: Discussionmentioning
confidence: 99%
“…ET1 is a potent vasoconstrictor peptide, and both ET1 and NO play pivotal roles in vascular homoeostasis (Kauser et al 2000). ET1 and NO work as negative feedback signals for each other (Li et al 2003, Oishi et al 2006, Kohan et al 2011. The reduced activation of eNOS is a characteristic of vascular endothelial dysfunction (Wohlfart et al 2008), and ET1 could promote early events leading to endothelial dysfunction and AS (Rautureau & Schiffrin 2012).…”
Section: Figurementioning
confidence: 99%
“…ET‐1 is a nanomolar potent peptide produced by diverse cell types throughout the body that functions in autocrine and paracrine signaling 9, 10. Multiple studies have demonstrated an increase in plasma ET‐1 levels in response to laboratory‐induced acute psychosocial stress in healthy, at risk, and diseased human subjects 2, 11, 12, 13, 14, 15, 16.…”
Section: Introductionmentioning
confidence: 99%